2019
DOI: 10.3390/met9090954
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures, Tensile Properties and Creep Characteristics of as-Extruded AZ91 Magnesium Alloy Containing Si, Ca and Rare Earth Elements

Abstract: Wrought AZ (Mg-Al-Zn) series alloys have attracted lots of researches, due to low cost, high strength and good formability. Few researches focus on creep characteristics of wrought AZ series alloys, which might be of significance to extensive use of low-cost wrought Mg-Al based alloy at elevated temperature. The microstructures, tensile properties and creep characteristics of as-extruded Mg-9Al-Zn-0.5RE-0.5Ca-0.5Si (wt.%, named AZXSE91000) alloy were investigated by optical microscopy (OM), scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In recent years a great deal of effort has been made to overcome this bottleneck problem. Recent studies have shown that the high-temperature mechanical properties of wrought Mg-Al based alloys, such as AZ91 [ 9 , 10 , 11 ], AZ80 [ 12 ], and AZ61 [ 13 ], can be improved by the trace addition of rare earth elements (REs). Because rare earth elements are non-renewable resources, and the addition of rare earth elements significantly increases the cost of the material, a more economical way of providing elevated-temperature strength of Mg-Al series alloys is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years a great deal of effort has been made to overcome this bottleneck problem. Recent studies have shown that the high-temperature mechanical properties of wrought Mg-Al based alloys, such as AZ91 [ 9 , 10 , 11 ], AZ80 [ 12 ], and AZ61 [ 13 ], can be improved by the trace addition of rare earth elements (REs). Because rare earth elements are non-renewable resources, and the addition of rare earth elements significantly increases the cost of the material, a more economical way of providing elevated-temperature strength of Mg-Al series alloys is urgently needed.…”
Section: Introductionmentioning
confidence: 99%